1995
DOI: 10.1007/bf01263638
|View full text |Cite
|
Sign up to set email alerts
|

Military expenditure and economic development: An endogenous growth perspective

Abstract: Abstract. This paper attempts to analyse the interrelationships between government and military expenditure and economic growth in particular, and between security and development in general, in a new framework. It has three novel features. First, the impact of military spending (as well as any other government spending which has similar externalities) is studied in an endogenous growth framework unlike most of the previous research in the field. Second, growth, welfare and security effects are studied simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 5 publications
0
8
0
2
Order By: Relevance
“…The dearth of studies that adopt a dynamic simulation modeling approach is rather surprising. Our sample of 93 studies includes only two studies that have adopted a calibration/simulation approach, namely Van Sinderen (1993) and Berthélemy et al (1995). There appear to be few studies that have adopted a computable general equilibrium (CGE) model approach.…”
Section: A Synthesis Of the Empirical Literaturementioning
confidence: 99%
“…The dearth of studies that adopt a dynamic simulation modeling approach is rather surprising. Our sample of 93 studies includes only two studies that have adopted a calibration/simulation approach, namely Van Sinderen (1993) and Berthélemy et al (1995). There appear to be few studies that have adopted a computable general equilibrium (CGE) model approach.…”
Section: A Synthesis Of the Empirical Literaturementioning
confidence: 99%
“…Russett (1970) showed that there is a substitution effect between military and social expenditures in the United States. Berthélemy et al (1995) showed a negative crowding-out effect between defence and education expenditures with a large negative effect on economic growth. 3 The debate on the economic consequences of military expenditures remains important in the post-Cold War period.…”
Section: Empirical Analysis Of the Negative Impacts Of Military Expenmentioning
confidence: 97%
“…(5) (Berthelemy, 1995). I E increases the skilled labor of the next period, while non-skilled labor increases with the natural growth rate of g N (Eqs.…”
Section: Supply-side Structurementioning
confidence: 98%
“…The details of military expenditure are described in Section 3.3. Berthelemy (1995) proposed that household utility is affected not only by individual consumption (C t /P t ) but also by non-military government expenditure (G t /P t ) and the security (Z t ) attained from military government expenditure. Government expenditures in both the non-military and military sectors cause an increase in the level of welfare and security, respectively.…”
Section: Supply-side Structurementioning
confidence: 99%
See 1 more Smart Citation